2009
DOI: 10.3892/or_00000633
|View full text |Cite
|
Sign up to set email alerts
|

Association of the ABCB1 3435C>T polymorphism and treatment outcomes in advanced gastric cancer patients treated with paclitaxel-based chemotherapy

Abstract: Abstract.We evaluated the frequency of ABCB1 polymorphisms (2677G/T>A and 3435C>T) and studied the association between the polymorphisms and clinical outcomes of paclitaxel-based chemotherapy in advanced gastric cancer patients. This study was performed in 43 gastric cancer patients and a control group consisting of 118 healthy volunteers. Patients were treated with paclitaxel combined with an infusional 5-fluorouracil and low-dose leucovorin. Genomic DNA from peripheral blood mononuclear cells was used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
5
16
1
1
Order By: Relevance
“…Variants at the 3435 position have been associated with shorter overall survival and worse progression free survival in paclitaxel-treated cancer patients [8, 9]. Variants at the 3435 and 2677 position have been implicated in higher risk of paclitaxel-induced neutropenia [17] and docetaxel treatment outcomes [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variants at the 3435 position have been associated with shorter overall survival and worse progression free survival in paclitaxel-treated cancer patients [8, 9]. Variants at the 3435 and 2677 position have been implicated in higher risk of paclitaxel-induced neutropenia [17] and docetaxel treatment outcomes [27].…”
Section: Discussionmentioning
confidence: 99%
“…A number of putative pharmacogenetic markers for paclitaxel outcomes, in breast cancer and in other solid tumors, have been evaluated [8-17]. Most of these studies focused on known mutations in biologically relevant candidate genes, such as CYP2C8, CYP3A4, and ABCB1, which code for the enzymes involved in paclitaxel metabolism and the transporters that influence paclitaxel disposition.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies reported an association with survival in 43 Chinese gastric cancer patients [113] and in 109 Korean patients with metastatic breast cancer [114]. Conversely, for various types of cancer, no association with survival or the occurrence of adverse effects was observed [115][116][117].…”
Section: Taxanesmentioning
confidence: 92%
“…ABCB1 polymorphisms were also tested as predictive biomarkers for chemotherapy efficacy for irinotecan and oxaliplatin in 5-FU-based treatment colorectal cancer patients with negative results [19]. rs1045642 was found to be associated with clinical outcomes after chemotherapy of paclitaxel combined with 5-FU in 43 advanced gastric cancer patients [20]. In 5-FU or capecitabine-treated patients, increased toxicity has been related to increased efficacy, such as in the case of DPYD and TYMS deficiency [21,22].…”
Section: -I Ii-iv P-value 0-i Ii-iv P-value 0-i Ii-iv P-valuementioning
confidence: 98%